Soil Moisture Monitoring Using Nodemcu Based Soil Moisture Sensor With Blynk Application Output - Asni Tafrikhatin; Ajeng Tiara Wulandari; sumarah, Jati; Irfan Nur Cahyadi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Currently, soil moisture monitoring is only done manually, which is less accurate, even though sometimes we need a soil moisture monitoring tool to determine the soil water content in plants. This research uses a Soil Moisture sensor to measure soil moisture and the NodeMCU ESP8266 microcontroller as the main controller. The system is designed to provide accurate and efficient soil moisture monitoring through the Internet of Things (IoT). The integration of Blynk as a monitoring application offers easy access to real-time soil moisture data via mobile devices. This system is designed to help users monitor soil moisture in real-time using NodeMCU as the main platform and Blynk for user interaction. Through this system, it is expected that users can avoid the risk of water shortages by knowing the soil water content in real-time. Based on testing, this soil moisture monitoring product has a success rate of 88.2% for soil moisture accuracy and an average user satisfaction rate of 60%.